Answer:
(X2+3)2
Step-by-step explanation:
First, you have to substitute in what f(x) equals for y since f(x) stands for y.
By doing this, the equation turns into (x2+3)2, because x2+3 is y, and 2 because the original equation way y2.
After you substitute, the answer is (x2+3)2.
Answer:87
Step-by-step explanation:
The solution of the radical equation is x = 5 / 3.
<h3>How to solve radical equation?</h3>
The radical equation can be solved by isolating x.
Therefore, the radical equation can be solved as follows:
√3x - 1 - 2 = 0
add 2 to both sides
√3x - 1 - 2 = 0
√3x - 1 - 2 + 2 = 0 + 2
√3x - 1 = 2
square both sides
√3x - 1 = 2
(√3x - 1 )² = 2²
Hence,
(√3x - 1 )² = 2²
3x - 1 = 4
Therefore, add 1 to both sides
3x - 1 = 4
3x - 1 + 1 = 4 + 1
3x = 5
divide both sides by 3
3x = 5
3x / 3 = 5 / 3
x = 5 / 3
Therefore, the solution of the radical equation is x = 5 / 3.
learn more on radical equation here: brainly.com/question/28442352
#SPJ1
The answer is C) (1,7)and (7,1). In order to find the correct answer ,just substitute the numbers for x and y in the problem,so:5(1)(7)+9=44 .35+9 =44,44=44 ,so that's true .Then check the other set of given numbers by substituting for x and y :5(7)(1)+9=44,35*1=35+9= 44,therefore 44=44 ,so both sides are true.*Also remember x is always the first number given,and then y.*
Answer:
Increase
Step-by-step explanation:
If you multiply the numbers it increases!